2021
DOI: 10.1001/jamanetworkopen.2021.7072
|View full text |Cite
|
Sign up to set email alerts
|

Association of Traumatic Injury With Adverse Pregnancy Outcomes in Taiwan, 2004 to 2014

Abstract: IMPORTANCE Literature has suggested that trauma among pregnant women is associated with an increased risk of adverse pregnancy outcomes. However, limited research has investigated the association of trauma with adverse pregnancy outcomes by using a national data set.OBJECTIVE To investigate the association between traumatic injury and adverse pregnancy outcomes. DESIGN, SETTING, AND PARTICIPANTSThis population-based cohort study of pregnant women in Taiwan linked 3 data sets, the Taiwan Birth Registry, Househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Our findings revealed that pregnant women who received treatment at clinical institutions within 3 days after crashes had an increased risk of adverse pregnancy outcomes. The finding was consistent with those of studies that indicated that such women hospitalised or treated at an emergency department due to injury had a higher risk of adverse outcomes 5 8 24. Relevant literature has shown that pregnancy-induced termination is also associated with an increased risk of haemorrhage among pregnant women 25.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings revealed that pregnant women who received treatment at clinical institutions within 3 days after crashes had an increased risk of adverse pregnancy outcomes. The finding was consistent with those of studies that indicated that such women hospitalised or treated at an emergency department due to injury had a higher risk of adverse outcomes 5 8 24. Relevant literature has shown that pregnancy-induced termination is also associated with an increased risk of haemorrhage among pregnant women 25.…”
Section: Discussionsupporting
confidence: 87%
“…Injury during pregnancy may result in adverse maternal outcomes, such as splenic rupture, uterine rupture, pelvic fracture, placental abruption and maternal death 5 6. Severe trauma has also been associated with a higher risk of premature delivery or fetal death 7 8. Injured pregnant women have a huge impact on maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal data have previously established that PTPs have worse outcomes in pregnancy compared with noninjured pregnant patients, with higher rates of preterm labor and associated complications (e.g., low birth weight and fetal death). 2,8,13,25,[27][28][29][30] However, there is a paucity of high-quality data on index trauma hospitalization outcomes for PTPs. This multicenter retrospective study encompassing 6 years of data from 12 Levels I and II trauma centers identified a FD rate of 10.7% in PTPs presenting at 24 weeks or later gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…While much of the currently available data focuses on catastrophic complications in PTPs (e.g., maternal and fetal death) and long-term pregnancy outcomes, 1,[3][4][5][6]25,27,[30][31][32][33] there is a paucity of data regarding predictors of FD for clinical decision making in terms of monitoring PTPs postinjury. In current practice, clinicians rely on the absence of abnormal findings to inform when it is safe to discharge a PTP from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to non-pregnant females, the occurrence of TBI in a pregnancy increases the risk of complications both to mother and foetus including increase rate of instrumental vaginal deliveries, unplanned caesarean sections, preterm birth, increased need of analgesia during labour and there will be an increased health impairment risk to neonate 3,23,45) . In addition pharmacologic therapies and diagnostic studies where the ionizing radiation is used will increase the risk teratogenicity, placental abruption, and risk of preterm labour 1) .…”
Section: Complicationsmentioning
confidence: 99%